Behavioral anomalies and fuel efficiency: Evidence from motorcycles in Nepal - Massimo Filippini; Nilkanth Kumar; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
Air pollution is a grave problem in urban areas of developing countries, with the transport sector being one of the largest contributors to emissions. A possibility to reduce carbon dioxide emissions would be for individuals to switch to more fuel-efficient vehicles. However, a gamut of behavioral anomalies and market failures have been known to inhibit individuals from investing in fuel-efficiency (due to the well-known "energy-efficiency gap"). In this study, we use novel data from Kathmandu, Nepal to understand the socio-economic and psychological determinants of three behavioral anomalies, namely present bias, loss aversion, risk aversion, as well as time preferences. In a second step, we evaluate the effect of these anomalies on the energy-efficiency gap in the choice of motorcycles of individuals. We find that present-biased individuals are less likely to invest in fuel-efficient motorcycles, and thus more likely to buy motorcycles having relatively high total lifetime costs. We also find that other factors such as income, as well as having applied for loans, play an important role in determining these choices. Our results suggest that behavioral anomalies may indeed pose as a hindrance to individuals making cost-minimizing (and also environmentally sound) investment decisions.
Keywords: D1; D8; Q4; Q5; 330; Passenger transport; Decarbonization; Switzerland; Computable general equilibrium model; Behavioral anomalies; Present bias; Fuel efficiency; Energy-efficiency gap; Motorcycles; Nepal